Influence of fatigue on upper limb muscle activity and performance in tennis - Rota, S.; Morel, B.; Saboul, D.; Rogowski, I.; Hautier, C. (Journal of Electromyography and Kinesiology, 2013)
The study examined the fatigue effect on tennis performance and upper limb muscle activity. Ten players were tested before and after a strenuous tennis exercise. Velocity and accuracy of serve and forehand drives, as well as corresponding surface electromyographic (EMG) activity of eight upper limb muscles were measured. EMG and force were also evaluated during isometric maximal voluntary contractions (IMVC). Significant decreases were observed after exercise in serve accuracy (-11.7%) and velocity (-4.5%), forehand accuracy (-25.6%) and consistency (-15.6%), as well as pectoralis major (PM) and flexor carpi radialis (FCR) IMVC strength (-13.0% and -8.2%, respectively). EMG amplitude decreased for PM and FCR in serve, forehand and IMVC, and for extensor carpi radialis in forehand. No modification was observed in EMG activation timing during strokes or in EMG frequency content during IMVC. Several hypotheses can be put forward to explain these results. First, muscle fatigue may induce a reduction in activation level of PM and forearm muscles, which could decrease performance. Second, conscious or subconscious strategies could lead to a redistribution of muscle activity to non-fatigued muscles in order to protect the organism and/or limit performance losses. Otherwise, the modifications of EMG activity could also illustrate the strategies adopted to manage the speed-accuracy trade-off in such a complex task.